Pengukuran Kualitas Layanan Sistem Informasi Poliklinik (SIPOLINK) dengan Metode Webqual 4.0 - Mustopa, Ali; Pratama, Eri Bayu; Nawawi, Hendri Mahmud (Program Studi Manajemen Informatika, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia, 2024)
The Polyclinic Information System (SIPOLINK) is designed to improve the quality of patient service by monitoring medical records more effectively and efficiently at the West Kalimantan Provincial Government Polyclinic. As an agency that handles health problems, the application of SIPOLINK provides significant added value for primary services, especially for users, namely all employees at the Polyclinic. This study aims to assess the quality of the SIPOLINK website services with the goal of improving service delivery to the community. The method used is Webqual 4.0, which includes three variables: usability quality, information quality, and interaction quality. Primary data was collected through a Likert scale questionnaire with 24 statements distributed to 30 respondents. Data analysis was conducted using descriptive statistical methods. The results indicate that interaction quality does not affect user satisfaction, while usability quality and information quality have a significant impact. The quality of SIPOLINK services affects user satisfaction by 87.3%, indicating that improvements in these areas can significantly enhance service delivery to the community.